Isostenosmylus ammirabilis sp. nov., a remarkable new species of lance lacewing (Neuroptera: Osmylidae) from the Colombian Andes - Ardila-Camacho, Adrian; Martins, Caleb Califre; Noriega, Jorge Ari (Zootaxa, 2020)
Isostenosmylus Krüger, 1913 is the richest genus of Osmylidae of the Neotropical region, with 17 described species so far, which are distributed mainly in the Andean region and in the South of Brazil and Paraguay. A new remarkable Colombian species of Isostenosmylus—I. ammirabilis sp. nov.—is herein described and illustrated. DNA barcode of mitochondrial gene cytochrome c oxidase subunit I (COI) for this species is also provided. Taxonomic keys for the genus are updated.